Excitons in a cylindrical GaAs Pöschl-Teller quantum dot - Mora-Ramos, M. E.; Barseghyan, M. G.; Duque, C. A. (Physica Status Solidi (b), 2011)
The exciton binding energy in a cylindrical quantum dot (QD) with Pöschl–Teller confining potential is studied with the use of the effective mass approximation and a variational calculation procedure. A GaAs prototype structure is particularly considered and both the spatially‐direct (DE) and spatially‐indirect (IE) exciton regimes are taken into account. We show that there is a significant effect of the Pöschl–Teller quantum well (QW) symmetry profile on the exciton properties in both configurations.